Poor 1st-year adherence to anti-osteoporotic therapy increases the risk of mortality in patients with magnetic resonance imaging-proven acute osteoporotic vertebral fractures - Chen YC (Patient Preference and Adherence, 2017)
Ying-Chou Chen,1 Wei-Che Lin2 1Department of Rheumatology, 2Department of Radiology, Kaohsiung Chang Gung Memorial Hospital, Chang Gung University College of Medicine, Kaohsiung, Taiwan, Republic of China Aim: Anti-osteoporotic therapy requires years of proper compliance to reduce the risk of fractures. This study investigated the effects of 1st-year adherence to anti-osteoporotic treatment on the risk of mortality in patients with magnetic resonance imaging-proven acute osteoporotic vertebral fractures after vertebroplasty.Patients and methods: This retrospective study included 294 patients (252 females; mean age, 73.93±7.18 years) with osteoporosis and acute vertebral fractures treated with vertebroplasty between January 2001 and December 2007. Sex, age, body mass index, comorbidities, previous hip fracture, number of vertebral fractures, 5-year re-fracture rate, and use of anti-osteoporotic therapy were recorded for each patient. Adherence was determined according to compliance and persistence for 1 year. Compliance was calculated as the medication possession ratio (MPR), and persistence as the time from treatment initiation to discontinuation. Poor adherence was defined as either non-compliance or non-persistence.Results: The MPR of the patients at 1 year was 55.1%, with a persistence rate of 69.4% and a poor adherence rate of 62.6%. Cox regression analysis revealed that poor adherence to medications was associated with a significantly higher risk of mortality after adjustment for potential confounders (hazard ratio [HR]: 1.75; 95% CI: 1.13–2.71). Poor adherence to medications was significantly associated with an increase in the rate of infection (HR: 4.56; 95% CI: 1.12–18.52), which was the most common cause of death.Conclusion: Poor adherence to anti-osteoporotic therapy significantly increases the risk of morality, possibly due to an increased risk of infection. Efforts should be made to improve adherence. Keywords: osteoporosis, vertebral fracture, adherence, mortality